Changes in latitude: overwintering survival of two Lilioceris cheni (Coleoptera: Chrysomelidae) biotypes in Florida. Issue 3 (4th March 2018) - Smith, Melissa C.; Overholt, William H.; Lake, Ellen C.; Diaz, Rodrigo; Manrique, Veronica; Hight, Stephen; Rohrig, Eric; Minteer, Carey R.; Wheeler, Gregory; Rayamajhi, Min; Bowers, Kristen; Kerr, Christopher
ABSTRACT: Lilioceris cheni is a successful biological control agent on the invasive yam, Dioscorea bulbifera in many areas in Florida, Georgia, Alabama and Louisiana. Two biotypes are available for release and come from significantly different centres of origin. The Nepalese biotype was collected at higher altitude and latitude sites, whereas the Chinese biotype was collected at slightly lower latitude and lower altitude. We hypothesised that Nepalese beetles would survive winter better in north Florida and that Chinese beetles would overwinter better in subtropical south Florida. We established sites in Homestead, Fort Pierce, Gainesville and Tallahassee, Florida to gauge the overwintering survival of each biotype. Beetles that overwintered in each site for one to three seasons were collected and followed to assess their reproductive capacity. In the final year of the experiment, we extracted fat bodies to determine effects of biotype and site. Nepalese beetles overwintered significantly better overall. Beetles survived better in the first study year (2013–2014). Both biotypes reproduced very well after surviving winter and beetles in Fort Pierce survived better than beetles in other regions and maintained a higher fat body. Nepalese beetles may have a wider ecological envelope – a decided advantage for a large region such as peninsular Florida. We suggest that current release programmes incorporate Nepalese beetles into their protocol to increase overwinter survival and establishment.